2012
DOI: 10.3390/polym4010020
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Behavior of Dendrigraft Polylysines in Water and Dimethylformamide

Abstract: Abstract:The four first generations of dendrigraft poly-L-lysine have been studied in dimethylformamide (aprotic solvent) and in 0.2 M NaCl aqueous solutions by isothermal translation diffusion, 1 H NMR and viscometry methods. The relationships between diffusion coefficient, intrinsic viscosity and molar mass have been determined for dendrigraft poly-L-lysines, and the scaling index values have been compared to classical trifunctional dendrimers. Dendrimers and dendrigraft poly-L-lysines exhibited similitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…The higher the degree of branching, the smaller is the size of the dendrigraft. We found that sizes calculated from the simulations of dendrigrafts 2 and 3 (with three and seven branching points in each side chain, respectively) are in good agreement with the existing experimental data for PLL dendrigrafts [ 28 , 29 ]. At the same time, the size of dendrigraft 1 (with linear side chains) is essentially greater than that of experimental ones and it is likely that this topology is not realized in real lysine dendrigrafts.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The higher the degree of branching, the smaller is the size of the dendrigraft. We found that sizes calculated from the simulations of dendrigrafts 2 and 3 (with three and seven branching points in each side chain, respectively) are in good agreement with the existing experimental data for PLL dendrigrafts [ 28 , 29 ]. At the same time, the size of dendrigraft 1 (with linear side chains) is essentially greater than that of experimental ones and it is likely that this topology is not realized in real lysine dendrigrafts.…”
Section: Discussionsupporting
confidence: 84%
“…The values of R g calculated from MD simulations of dendrigraft 2 and dendrigraft 3 (2.64 nm and 2.09 nm, respectively) belong to the interval of values R g = 1.65–2.65 nm ( R h = 2.14–3.43 nm) obtained by different experimental methods in [ 28 , 29 ], while our value of R g for dendrigraft 1 is essentially higher than for the experimental ones.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…Then the core of Angio-DOX-DGL-GNP was dissembled when exposed to MMP-2 overexpressed in TNBC [ 24 26 ] and released the small-sized Angio-DOX-DGL-PEG, facilitating the delivery of NPs to the core area to kill more viable cells [ 24 , 27 ]. Specifically, in consideration of the uniformly small size (4 ~ 7 nm) and structural modifications for specific biomedical applications, DGL was employed as the small-sized carriers linked with angiopep-2 [ 28 30 ]. Moreover, with the aim to examine the ability of Angio-DOX-DGL-GNP's targeting effect and therapeutic effect, DOX was attached to DGL via a pH-sensitive cis-aconitic anhydride bond [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical characterization of dendrimers, and particularly DGLs is crucial for these applications as their macromolecular dimension and behavior in aqueous solution determine their biomedical efficiency . Their average molecular weights (connected to their average degrees of polymerization, DP) are also important for establishing a structure–property relationship.…”
Section: Introductionmentioning
confidence: 99%